2013
DOI: 10.5935/paet.v6.n2.08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the different periods of weed interference on lettuce in protected cultivation

Abstract: The objective of the study was to evaluate the effect of different periods of the interference of species of weeds on the lettuce in greenhouses. It was used a randomized experimental design in blocks with four replications, evaluating four period prior to interference -PPI, which were: 0, 10, 15, 20, 25 days after the transplantation. It was determined the number by species (m -2 ) and fresh and dry mass of weeds (g m -2 ), the head diameter (cm), number of leaves and fresh and dry mass of shoots (g m -2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The few studies that have reported on the critical period of weed interference in lettuce indicate that weed control in just the first couple of weeks after crop transplanting is crucial to avoid yield loss [3,15,16]. These studies provide valuable information regarding agronomic and economic aspects, but they do not investigate other positive externalities possibly related to optimizing weed control.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have reported on the critical period of weed interference in lettuce indicate that weed control in just the first couple of weeks after crop transplanting is crucial to avoid yield loss [3,15,16]. These studies provide valuable information regarding agronomic and economic aspects, but they do not investigate other positive externalities possibly related to optimizing weed control.…”
Section: Introductionmentioning
confidence: 99%
“…Several weeds interfere with lettuce growth, such as: smooth pigweed (Amaranthus hybridus), jamaican crabgrass (Digitaria horizontalis), nutgrass (Cyperus rotundus), milkweed (Euphorbia heterophylla), and benghal dayflower (Commelina benghalensis) (Santos et al, 2003;Giancotti et al, 2010;Nascimento et al, 2013). Santos et al (2003) emphasized that plants of the genus Amaranthus interfere with early lettuce growth due to light interception by their taller canopy, which makes it an important genus in lettuce cultivation areas.…”
Section: Introductionmentioning
confidence: 99%